Organizational Collaborative Relationships in Agile Contexts: A Mapping Study - Fortuna, Alessandra; Santos, Gleison (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2025: Anais do XXI Simpósio Brasileiro de Sistemas de Informação, 2025)
Context: Collaboration is used in intra- and inter-organizational relationships as a supportive practice to help organizations remain competitive. Agile methods and practices facilitate collaboration in relationships and interactions among software development team members, customers, and stakeholders. Problem: There are still gaps in understanding the effective use of agile methods in different organizational relationships (intra- and inter-organizational). Solution: This study aims to identify the state-of-the-art regarding organizational collaborative relationships supported by agile methods and practices. IS Theory: The study is analyzed from the perspective of General Systems Theory. Method: A systematic literature mapping was conducted. Summary of Results: From 37 studies, evidence was found that using agile methods and practices in different organizational collaborative relationships can positively impact aspects such as innovation, knowledge transfer, and management practices. Additionally, challenges were identified, especially regarding difficulties with collaboration, communication, and coordination in large-scale developments or those involving many actors. Contributions and Impact on the IS Field: The results enabled an understanding of the motivations behind agile adoption in different organizational collaborative relationships, identifying how these approaches influence collaborative interactions and relationships and presenting the managerial aspects involved. The findings are expected to help managers and organizations enhance collaborative practices by providing a comprehensive view of this topic’s motivations, benefits, and challenges.